Unpacking Etimology Urban Space Quality: Menuju Definisi Umum - Wiliarto Wirasmoyo; Ikaputra (Arsir: Jurnal Arsitektur, 2024)
The concept of "urban" is often understood from various perspectives, but not comprehensively. This writing aims to provide a deeper understanding of the concept of urban, particularly urban space quality. The definition of urban space quality has not been fully captured, which motivates the need for a more in-depth exploration of the term. The research problem is the lack of a comprehensive understanding of the concept of urban space quality, leading to the absence of a universally accepted definition. The aim of this article is to examine the suitability of the use of the term "urban space quality" to provide a reference for its usage. The article utilizes a literature review, drawing from credible and traceable sources such as books, national-international journals, dictionaries, official documents, and previous studies related to the etymology of urban, urban space, and urban space quality. Urban space is defined as an external space contributing to the city's structure, communication, and social interaction. The concept of urban space quality remains multifaceted, with varying interpretations and dimensions, including safety, livability, environmental conditions, and social development. The findings underscore the complexity of urban space quality and the need for a comprehensive understanding of its parameters and factors.